Bank-specific capital requirements and capital management from 1989-2013: Further evidence from the UK - de-Ramon, Sebastian J.A.; Francis, William B.; Harris, Qun (Journal of Banking & Finance, 2022)
We examine how bank-specific capital requirements affect banks’ capital ratios and balance sheet composition over the period 1989-2013. We find that higher requirements, even when not binding in a regulatory sense, result in higher bank capital ratios, achieved by a combination of asset contraction, risk reduction and capital raising strategies. We find that after the 2007-09 financial crisis, banks place greater emphasis on raising capital, but that they continue to focus first on raising lower-quality capital. Our results have implications for evaluating the efficacy of bank-specific capital requirements as a policy tool to influence bank balance sheet behavior and resilience.